Republic of Belarus : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper presents an assessment of financial system stability in Belarus. The findings reveal that the state-dominated financial sector of Belarus confronts several critical challenges. Deep and long-standing structural problems and negative external spillovers are distorting the credit channel and overall financial stability. Financial sector contingent liabilities are on the rise, accentuating an already weak fiscal situation. The government is directing a large proportion of loans from state-owned banks to unhedged state-owned companies. Foreign currency liquidity risk is high, and transition to independent and risk-based oversight of the financial sector is urgently required.